Analysis of partial least square estimation process and control of distillation column process - Nurul Hamizah, Baharan (2006)
Distillation columns are the most important separation process in unit operation. The used of distillation column is widely in industries especially in chemical and petroleum industries for separating the substances based on the differences of substances volatility. To incentive economic and control the quantity of the product in the industry, on-line handling the control system is needed and the MATLAB programming is proposed. In this thesis, the distillation column programme in MATLAB is used to analysis of Partial Least Square (PLS) Estimation Process and Control of Distillation Column Process. The analysis worked by generated the data for dynamic response and the base case control in nominal condition. Based on the generated data the estimation product is predicted by using the PLS estimator to maintain the desired product when the disturbance occurs. The estimation result show that the prediction data is nearest to actual data. Based on the result the distillation column control programme is proposed to be the best control process.